Pharmacoeconomic analysis of Flemoclav Solutab® use in adult patients with acute sinusitis in routine outpatient clinical practice in Russia - A. S. Kolbin; I. A. Vilum; M. A. Proskurin; Yu. E. Balykina (Izdatelstvo OKI, 2018)
For the first time in Russia, the pharmacoeconomic analysis of Flemoclav Solutab(R) use was carried out in the therapy of acute sinusitis in adults based on the data of a prospective observation research in routine out-patient practice. In terms of the results of the pharmacoeconomic model developed on the basis of the research data FlemENT the following regularities were found. The use of medicine of Flemoclav Solutab® as a therapy of acute sinusitis is economically reasonable from the point of view of the cost-effectiveness ratio. The strategy of Flemoclav Solutab® demonstrated high clinical benefits and the best safety profile with the smallest cost of adverse event therapy among the studied medical treatment technologies of this group of patients in comparison with the strategies of Amoksiklav® and Augmentin® SR. The use of Flemoclav Solutab® in comparison with the strategy of Amoksiklav® and Augmentin® SR is more economically preferable technology on the account of budget impact analysis: the use of medicine of Flemoclav Solutab® enables to keep considerable budget funds of health care - up to 5 180 193 rub, and also to treat by means of this strategy up to 725 patients.